Outcomes of topical phenytoin in the management of traumatic wounds - Kumar, C Shyam (J Clin Orthop Trauma, 2020)
INTRODUCTION: Regular dressing of traumatic wounds is of paramount importance for healing. Phenytoin, an anticonvulsant, is thought to promote wound healing through multiple mechanisms, including fibroblast proliferation, granulation tissue formation, antibacterial activity, and pain alleviation. AIM: To assess the effect of topical phenytoin on traumatic wound healing in terms of granulation tissue formation, pain alleviation, and time taken for wound healing. METHODOLOGY: Fifty patients with traumatic wounds were divided into equal and comparable groups. After cleaning the wound, phenytoin dressing was done in the study group and saline dressing in the control group. Thereafter, regular dressings of the wounds were done, and healing was assessed on day 14 and day 21. RESULTS: On day 14, the wound surface area, percentage of granulation tissue, VAS score amongst cases was 39.4 ± 29.75 cm(2), 82.12 ± 9.71%, 4.52 ± 1.08, and that of controls was and 51.28 ± 25.33 cm(2), 62.72 ± 9.01%, 6.52 ± 1.22, respectively. On day 21, the wound surface area, percentage of granulation tissue, VAS score amongst cases were 29.4 ± 29.88 cm(2), 92 ± 4.46%, 2.8 ± 0.94, and that of controls were 38.92 ± 23.24 cm(2), 78.56 ± 8.19%, and 4.88 ± 1.17, respectively. The time taken for wound healing was 21.76 ± 5.28 days amongst cases and 31.64 ± 8.31 days amongst controls. Staphylococcus aureus was the commonest organism isolated in both the groups. On day 14,18(72%), wounds in the study group showed negative culture, whereas, in the control group, it was negative in 12 (48%) patients. The rate of granulation tissue formation was higher in cases when compared to controls amongst smokers and diabetics. The difference in all these parameters between the groups was statistically significant (P-value <0.05). DISCUSSION AND CONCLUSION: We observed a considerable increase in granulation tissue formation, pain alleviation, and reduction in time taken for wound healing. Topical phenytoin is a safe, effective, readily available, and frugal agent that can accelerate wound healing through its multimodal action, thus reducing patient morbidity and economic burden. MESH TERMS: Phenytoin, Wound healing, Topical, Ulcer, Anticonvulsant, Granulation Tissue, Saline dressing.